Socioeconomic impact of the COVID-19 pandemic among plastic surgeons in Brazil - Renan Diego Américo Ribeiro; Igor Castro Carneiro; Gustavo Moreira Clivatti; Laielly Abbas; Gustavo Gomes Ribeiro Monteiro; Dov Goldenberg; Rolf Gemperli (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: Global sanitary crisis caused by the spread of COVID-19 induced many health services to stop performing non-urgent surgical procedures. In the scenario of plastic surgery, where most procedures are elective, socioeconomic consequences are estimated for these specialists. The objective of this study is to measure this impact. Methods: Effects of the pandemic within the clinical practice of Brazilian plastic surgeons were investigated through an online questionnaire addressed to members of the Sociedade Brasileira de Cirurgia Plástica. Results: A survey was applied to 645 surgeons. Most respondents reported operation restrictions on procedures and income reduction, especially in regions severely affected by the pandemic. Plastic surgeons with more than 10 years of experience were the most affected. High contamination rates, mental overload, decreased physical activity, and psychiatric medications have also been reported. Conclusion: COVID-19 pandemic brought changes to the personal and professional life of the Brazilian plastic surgeon. Due to the significant reduction in the workload, there were financial impacts on specialists from all country regions, besides physical and mental health issues. Adaptations were mandatory to maintain services and explore new areas of activity to supply the low demand for cosmetic surgery during the crisis.